Nutritional value of sorghum-sudangrass hybrids (Sorghum bicolor x Sorghum sudanense) harvested at different stages of maturity - Pedro Dias Sales Ferreira; Lúcio Carlos Gonçalves; José Avelino Santos Rodrigues; Diogo Gonzaga Jayme; Eloísa de Oliveira Simões Saliba; Otaviano de Souza Pires Neto; Diego Soares Gonçalves Cruz; Felipe Antunes Magalhães; Gabriel de Oliveira Ribeiro Júnior; Felipe Antunes Magalhães; Frederico Osório Velasco (Semina. Ciências agrárias : revista cultural e científica da Universidade Estadual de Londrina, 2015)
The aim of this work was to evaluate the nutritional value of four sorghum-sudangrass hybrids harvested at four different stages of maturity. The hybrids evaluated were BR800, BRS810 (bmr), BRS802 and 156x2784. Hybrids were harvested at 52, 61, 67 and 74 days after seeding. BRS802 and BRS810 (bmr) are sorghum-sudangrass hybrids isogenic pairs that are distinguished only by the presence of bmr-6 mutation on BRS810. Samples were analyzed for dry matter (DM), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF) and acid detergent lignin (ADL) content and in vitro DM and NDF digestibility (IVDMD and IVNDFD). Interaction between hybrid and stage of maturity was observed for NDF, ADF, IVDMD and IVNDFD. A linear increase in DM content was observed with increasing stage of maturity. A quadratic effect was observed for CP content with increasing stage of maturity, and the maximum CP value was estimated to be with 55.8 days. The hybrid BR800 had the highest CP content (12.5%) and the hybrids BRS 802 and 156x2784 the lowest CP content (9.7 and 10.3%, respectively) for all stages of maturity evaluated. A quadratic effect in NDF content was observed with increasing stage of maturity for the hybrids BR800, BRS810 (bmr) and BRS802 with the maximum values estimated to be with 62.0, 61.7 and 60.4 days after seeding respectively. With 52 and 67 days after seeding the hybrid BRS810 (bmr) had the lowest NDF content (64.2 and 66.4%, respectively). The isogenic pair, hybrids BRS802 and BRS810 (bmr), had a linear decrease in ADF ontent with increasing stage of maturity, and with 52, 61 and 67 days after seeding the bmr hybrid had lower ADF content compared to its counter pair (BRS802). No linear or quadratic effect with increasing stage of maturity was observed for ADL content. The hybrids BRS802 and 156x2784 had the highest ADL content (4.42 and 4.16%, respectively) regardless of the stage of maturity. BRS810 (bmr) had the lowest ADL content (2.49%) and intermediate value was observed for BR800 (3.69%). The hybrid BRS810 (bmr) had higher IVDMD and IVNDFD than its isogenic pair (BRS802) for all stages of maturity evaluated. The bmr-6 mutation increased the nutritional value of the sorghum-sudangrass hybrid through reduction in the NDF, ADF and ADL content and increases in CP, IVDMD and IVNDFD. Comparing the normal hybrids (non bmr), the hybrid BR800 stood out because of its lower ADF and ADL content and higher IVNDFD.